Toughening mechanism and delayed fracture analysis of 4145H steel under intercritical quenching heat treatment process - Zhuoran Feng; Zhiqiang Li; Rou Liang; Zhuo Song; Hua Hou; Yuhong Zhao (Journal of Materials Research and Technology, 2023)
Tuning thermal treatment schedule has been confirmed as an effective technical route for achieving optimum properties of steels. In the present work, the intercritical quenching tempering(IQT) process was applied to steel 4145H for oil drilling tools, and the performance enhancement and delayed fracture mechanism of the IQT process were comprehensively elucidated using multiscale characterization methods and various mechanical tests. Compared with the quenching and tempering(QT), the IQT process results in a separate island ferrite plus finely tempered sostenite organization, which reduces the dislocation density in the tempered organization and increases the proportion of recrystallized grains. Due to the grain refinement effect of multiple quenching, the pristine austenite grains were refined by 58 %. At the same time, the proportion of large-angle grain boundaries increased from 68.6 % to 80.3 %. The results of the mechanical property tests show that the intercritical 790 °C quenching treatment and tempering at 600 °C exhibits a tensile strength of 1087 MPa, a high elongation of 21.72 %, and a high impact work of 104 J compared to QT. The improved impact toughness is mainly attributed to the grain refinement effect of multiple quenching and the large-angle grain boundaries provided by the composite ferrite organization and M23C6 carbides. The impact of different ratios of large-angle grain boundaries on crack extension was also evolved by means of the crystal phase field, and the delayed fracture effect of large-angle grain boundaries was verified.